The Effect of BPJS Online Tiered Referral System Health on Patient Satisfaction at Royal Prima Hospital - Ginting, Johannes Bastira (Jurnal Prima Medika Sains, 2024)
The National Health Insurance System (JKN), managed by BPJS, is a strategic initiative of the Indonesian government to ensure access to affordable and quality healthcare. This study aims to evaluate the effect of implementing an online tiered referral system on patient satisfaction at Royal Prima Hospital. The method used was non-experimental quantitative research with a descriptive approach and associative analysis conducted at Royal Prima Hospital Medan from February to March 2019. Data was collected through an online-based questionnaire survey involving 100 respondents and analyzed using the Chi-Square test and multiple logistic regression. The results of the analysis showed a significant relationship between several variables and patient satisfaction, such as ease of requirements (p = 0.010), service procedures (p = 0.017), service time (p = 0.006), cost efficiency (p = 0.001), and facilities/ infrastructure (p = 0.020). In contrast, variables that did not show a significant relationship included product specifications (p = 0.268), executor competence (p = 0.200), executor behavior (p = 0.103), and complaint handling (p = 0.074). From the multivariate analysis, the cost variable showed the highest Odds Ratio (OR) of 7.516, indicating that patients who felt cost-efficient had a 7.516 times greater chance of being satisfied. This study confirms that cost efficiency, service speed, and procedure quality significantly affect patient satisfaction, providing insight for BPJS Kesehatan in improving the quality of health services in Indonesia.